Carbon dopants carriers facilitators as agents for improving hole extraction efficiency of cobalt tetraoxide nanoparticles employed in fabrication of photodetectors. (September 2021) - Popoola, AbdulJelili; Gondal, Mohammed A.; Oloore, Luqman E.; Buliyaminu, Ismail A.; Popoola, Idris K.; Aziz, Md. Abdul
Graphical abstract: Highlights: Development of low cost and high performance, versatile photodetectors based on perovskite materials is main focus of this work. we employed carbon – doped cobalt tetra-oxide nanoparticles substrate as an efficient hole extraction material in fabrication of simple sandwiched type architecture of perovskite based photodiodes. lead free perovskite photodetectors are presented along with investigating the effect of carbon dopant hole transport material on augmenting the over all performance of these detectors. The linearity and stability of the photodetectors over wide range of light intensities and 100 optical switching cycles were also demonstrated. Abstract: (CH3 NH3 )3 Bi2 I9 perovskites have attracted enormous attention due to their lower toxic and more stable nature than CH3 NH3 PbI3 counterparts. However, higher bandgap and lower carrier mobility hinder the application of (CH3 NH3 )3 Bi2 I9 in optoelectronics. Hence, we employed carbon doping of Co3 O4 hole extractors to reduce the bandgap of (CH3 NH3 )3 Bi2 I9, minimize non – radiative recombination rate and improve surface morphology of the (CH3 NH3 )3 Bi2 I9 particles . Consequently, photodetectors based on carbon-doped Co3 O4 display reduced internal resistance, high photocurrent and low dark current values. The fabricated photodetectors display high responsivity (1.56 × 10 6 μA/W), high detectivity (5.74 × 10 12 Jones), high sensitivity (8.23 × 10 3 ) and fast optical switching times (< 10 ms) values under device testing conditions of 2.0 V bias voltage, 10 mW/cm 2 power intensity of solar illumination and ambient room conditions. The linearity and stability of the photodetectors over wide range of light intensities and 100 optical switching cycles were also demonstrated respectively.